The old age pensions and gender equality in Lithuania - Skučienė, Daiva (Socialinė teorija, empirija, politika ir praktika, 2006)
The purpose of the article is to extend Lithuanian pension system old age benefits analysis from viewpoint of gender equality. The article is divided in several parts: first- preretirement gender income inequality; second - the types of pension systems and gender old age pension’s inequality; third - Lithuanian gender pension benefits and the causes of differences. Equal gender treatment in all areas of life seems solve all problems, which could arise in gender inequality area. Unfortunately, traditional labor division in family and thus in a whole society, conditioned quite unequal economic gender outcomes. Preretirement gender inequality produces gender inequality after retirement. In generally women have lower average wage than men; care periods are inherence for women labor and this is the cause why women participation period in labor market is shorter; earlier women retirement also decreased the number of years participation in labor market; generally women life expectancy is longer than men, this means, that they consume pension longer. Lithuanian social insurance system provides care period guarantees for future pension benefit, but childcare under I year is guaranteed only 60% (now 70%) previous wage. Childcare from 1 until 3 years is guaranteed only basic pension. Child nursing period decrease pension benefit about 15% (until 2001 01 01 it was 20%). According to pension calculator in Lithuania and choose several wages and age options, we could see, that outcomes are unfavorable for women. It is probability, that gender inequality after retirement will increase. Hence, pension system in Lithuania have unresolved gender equality problems.